The cemeteries of XIX century at north of Madrid and its urban transfor mation. - Jiménez Blasco, Beatriz Cristina (Anales de Geografía de la Universidad Complutense, 2009)
Four cemeteries were constructed by the first half of the 19th century in Madrid in the north of the city, in the oriental sector of the neighborhoods of Arapiles and Vallehermoso of Chamberí district. Its closing was produced in 1884, but they did not disappear up to the second third of the 20th century. The impact of these cemeteries in the urban space is evident, it supposed the paralyzation of the construction on a considerable quantity of soil and a devaluation of the neighborhood. The areas that had been occupied by the cemeteries had a different urbanization in every case. Pendant la première moitié du siècle XIX ont été construits à Madrid quatre cimetières au nord de la ville, dans le secteur oriental des actuels quartiers d’Arapiles et Vallehermoso du district de Chamberí. Sa clôture s’est produite en 1884, mais ils n’ont pas disparu jusqu’à le deuxième tiers du XXe siècle. L’impact de ces cimetières dans l’espace urbaine est évident, cela a supposé l’immobilisation de la construction sur une quantité considérable de sol et une dévalorisation du quartier. Les terrains qui avaient été occupés par les cimetières ont eu une différente urbanisation dans chaque cas.